2012
DOI: 10.1111/j.1468-0297.2012.02496.x
|View full text |Cite
|
Sign up to set email alerts
|

Choice of NHS‐Funded Hospital Services in England

Abstract: This article examines the choice of hospital for elective hip replacements amongst patients in England, using patient-episode level data from the Hospital Episodes Statistics records. The article is primarily methodological: we estimate a demand model that allows for heterogeneity across observed patient characteristics and demonstrate how to use this model to simulate the effect of mergers between hospitals. Our article contributes to the empirical literature on hospital choice and provides a novel method for… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

10
101
0
3

Year Published

2015
2015
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 93 publications
(114 citation statements)
references
References 14 publications
10
101
0
3
Order By: Relevance
“…Novel to the literature on university choice, we also examine how the impact of league tables on demand is influenced by competition, as given by the number of alternative providers in respective subject-department groupings. Consistent with predictions derived from economic theory and empirical evidence in other markets (Beckert et al, 2012;Gaynor and Town, -4 -2011), we find that the elasticity of demand with respect to league table rankings to be greater in courses in which universities compete more strongly with one another.…”
Section: Introductionsupporting
confidence: 76%
See 2 more Smart Citations
“…Novel to the literature on university choice, we also examine how the impact of league tables on demand is influenced by competition, as given by the number of alternative providers in respective subject-department groupings. Consistent with predictions derived from economic theory and empirical evidence in other markets (Beckert et al, 2012;Gaynor and Town, -4 -2011), we find that the elasticity of demand with respect to league table rankings to be greater in courses in which universities compete more strongly with one another.…”
Section: Introductionsupporting
confidence: 76%
“…Additionally, the article is instructive for recent debates in economics about salience, and the propensity of market actors to pay disproportionately more attention to information presented in some formats than others (Chetty et al, 2009;Falkinger, 2008;Hirshleifer and Teoh, 2003). Our findings also relate to work in industrial organization and the under-researched question of how demand responsiveness to beliefs about quality is moderated by the degree of market competition (Beckert et al, 2012;Gaynor et al, 2012;Porter, 1974). The present study is additionally of interest to decision-makers at both university and departmental levels who have increasingly confronted questions about the pay-offs from investments to improve student satisfaction scores and popular league table rankings (Hazelkorn, 2008;The Economist, 2013).…”
Section: Introductionmentioning
confidence: 67%
See 1 more Smart Citation
“…Existing work on hospital choice has focused on which hospital patients choose, taking the set of patients as given [Beckert et al, 2012;Ho, 2006;Kessler and McClellan, 2000] 1 . However, for most nonemergency health conditions, hospital care can be delayed or avoided.…”
Section: Introductionmentioning
confidence: 99%
“…Here we exploit variation in the relative distance to the nearest privately owned hospital over time, within regions where supply constraints remain xed. Existing work has demonstrated that patients show a strong preference for shorter distances [Beckert et al, 2012;Kessler and McClellan, 2000], whereas administrative supply constraints over this period operated at a broader geographical level, with England divided into 152 administrative areas tasked with funding health care for their residents. To identify an impact of privately owned hospital on demand, our baseline results use the enhanced panel data set to estimate xed eects models, which controls for time trends within the wider administrative area.…”
mentioning
confidence: 99%